CHESS IS A FIELD WHERE INTELLIGENCE, THINKING AND IDEAS GROW (American Journal of Interdisciplinary Research and Development, 2024)
In the article, the history of the development of the sport of chess abroad and in our country is looked at, and by teaching blind and visually impaired children to play chess, their logical thinking and will are formed, along with the development of their attention, perception, thinking, memory, and vocabulary through the use of chess games. in one line, the thoughts on how to prepare them for social life in some sense are highlighted.